Comportamento da percepção subjetiva de esforço após aplicação de diferentes métodos de progressão de treinamento aeróbico em homens saudáveis - Luz, Roquefelix Silva (2013)
Understanding the mechanisms of perceived exertion has always been a challenge because it is asubjective object of study. Since its conception until the present day many studies seeking to understand the correlations of rating of perceived exertion (RPE)with several physiological mechanisms. Little is known about the possible changes that may have RPEafter a period of aerobic training. This lack of studies about correlation of RPE and heart rate (HR), specificallythe behavior after training period,motivated this study. The main objectiveswereto compare the behavior of RPEand HR before and after trainingperiodin each group and between groups, and the correlation between RPE and HR.This study examined the behavior of RPE and HR during cardiopulmonary exercise testing in subjects who performed three different aerobic training programs for a period of 13 uninterrupted weeks. The groups took three forms ofperiodization:step load, growing load and ondulatory load. The differences in loaddistributions were related to the presence or absence ofreduced intensity and howthe load increase. In the statistical analysis we used the Wilcoxon test to evaluate the RPEbefore and after within the group and the Mann-Whitney test for comparisons between groups of RPE. To analyze the behavior of the HR, weused the paired Student’st-testfor each group and the Student’s t-testfor independent samples when comparing the groups. The correlation between RPE and HR was obtainedthrough Pearson correlation. The level of significance was set up at p <0.05. It was found that only the Gs showed differences in the behavior of the RPEwhen comparing the initial and final tests, with significant reduction of the values. The HR was modified in all groups having reducing of values in all groups, except for the last stage of ondulatory group. Comparing the valuesofRPEand HRbetween groupsthe differences occurredoccasionallyin somestages,without the ability toconfirma direct relationshipbetween the formatsofperiodizationand these variables